Integration Of The Therapeutic Architecture Approach In Public Buildings: Evaluation Of Priority Improvement Indicators - Utari, Cokorda Istri Arina Cipta; Prasandya, Km. Deddy Endra; Nugraha, Putu Gede Wahyu Satya (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2025)
Mental health issues have become a pressing concern in the modern working environment, particularly among public service workers who are exposed to persistent occupational stress. Built environments play a critical role in mitigating psychological strain, and therapeutic architecture offers a promising spatial intervention to address mental well-being. This study investigates the application of therapeutic architectural principles in a public service building, Sewaka Dharma, located in Denpasar, Indonesia. Using the Joint Multivariate Preference (JMP) method, the research evaluates user perceptions across six core dimensions of healing design, sense of personal control, social support, positive distractions, connection to natural views, elimination of environmental stressors, and the ability to engender positive feelings. Data were collected through structured questionnaires distributed to building users, focusing on 26 sub-indicators associated with the aforementioned variables. The results show that five indicators presence of indoor water elements, availability of entertainment facilities, access to natural outdoor views, integration of interactive art, and access to food services scored significantly below the overall mean. These findings highlight specific spatial deficiencies that limit the building’s restorative function and user comfort. The study contributes practical recommendations for public facility improvements by emphasizing evidence-based spatial design strategies that enhance psychological resilience and support mental health in the workplace.